2018
DOI: 10.1021/acs.oprd.8b00109
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Telescoped Process for Preparation of N,O-Chelated Diarylborinates

Abstract: A telescoped process has been developed for practical preparation of N,O-chelated four-coordinate diarylborinates via direct reaction of N,O-chelate ligands with a diarylborinate solution prepared by removal of magnesium via precipitation from a one-pot reaction of aryl bromides, magnesium, and tributylborate. Ten N,O-chelated diarylborinates of representative N,O-chelate ligands of 2-picolinic acid, quinolin-8-ol, N-dimethylglycine, and amino alcohols were readily obtained in good yields. The telescoped proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…4 a gave a remarkably lower yield for 3 aa (74 %) (Table 2, entry 12). Attempts to use 0.1 mol % PdCl 2 (PPh 3 ) 2 as catalyst led to a low yield (49 %) for 3 aa, but still the highest one among the tested palladium catalysts, e. g. PdCl 2 (dppf) (41 %), PdCl 2 (dppm) (33 %), PdCl 2 (dppe) (28 %), PdCl 2 (dppb) (22 %), PdCl 2 (binap) (12 %) and Pd-PEPPSI-IPr (35 %) (Table 2, entries [13][14][15]. Again, almost no reaction was observed with PdCl 2 , Pd(OAc) 2 or Pd/C under the otherwise identical conditions (Table 2, entry 16).…”
Section: Resultsmentioning
confidence: 99%
“…4 a gave a remarkably lower yield for 3 aa (74 %) (Table 2, entry 12). Attempts to use 0.1 mol % PdCl 2 (PPh 3 ) 2 as catalyst led to a low yield (49 %) for 3 aa, but still the highest one among the tested palladium catalysts, e. g. PdCl 2 (dppf) (41 %), PdCl 2 (dppm) (33 %), PdCl 2 (dppe) (28 %), PdCl 2 (dppb) (22 %), PdCl 2 (binap) (12 %) and Pd-PEPPSI-IPr (35 %) (Table 2, entries [13][14][15]. Again, almost no reaction was observed with PdCl 2 , Pd(OAc) 2 or Pd/C under the otherwise identical conditions (Table 2, entry 16).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Zou et al also showed the importance of the workup conditions ( Scheme 3 ) [ 15 ]. As just mentioned, they observed the selective formation of the p -tolylborinic ester 9 when using tributyl borate B(O n -Bu) 3 , instead of B(OMe) 3 or B(O i -Pr) 3 .…”
Section: Formation Of Two Carbon–boron Bondsmentioning
confidence: 99%
“…In general, good yields are obtained whatever the substitution pattern on the aromatic ring. Furthermore, electron-withdrawing (i.e., 12a [ 24 ], antibacterial agent 13f [ 25 ] , 13h [ 15 ] ) and -donating ( 12b [ 6 , 26 ], 12d ) [ 7 ] substituents are tolerated, as well as napththyl groups (i.e., 12g , a 1,2-diol complexing agent for absolute configuration prediction) [ 27 ]. However, the reaction is less efficient for para vinyl-substituted borinic acid 13e [ 28 ], probably because of the potential reaction of the styrenyl moiety with the Grignard reagent.…”
Section: Formation Of Two Carbon–boron Bondsmentioning
confidence: 99%
See 2 more Smart Citations